Response of blood gas tensions to aminophylline and isoprenaline in patients with asthma. Issue 6 (November 1967) - Tai, E.; Read, John
Abstract : Aminophylline and isoprenaline, two drugs widely used in the management of asthma, have a pulmonary vasodilator action as well as a bronchodilator action. If regional pulmonary vasoconstriction in poorly ventilated parts of the lungs is a significant compensatory phenomenon in asthma, the effects of administration of these agents on gas exchange would depend on the relative magnitudes of bronchodilator action and pulmonary vasodilator action in the individual patient. If vasodilator action were greater than bronchodilator action in significant portions of the lungs, maldistribution of ventilation-blood flow ratios would increase and arterial oxygen tension might fall. In 40 patients with chronic asthma, arterial blood gas tensions, minute ventilation, alveolar-arterial oxygen tension gradient, physiological dead space/tidal volume ratio, and oxygen consumption were measured before and at intervals up to 20 to 40 minutes after the administration of various agents: in 13 patients, 250 mg. of aminophylline intravenously; in 16 patients, six deep inhalations of 1% isoprenaline aerosol; in 11 patients, after various control procedures. There were no significant changes following the control procedures. Administration of both aminophylline and isoprenaline was followed by increases of F.E.V.1·0 and increases of minute ventilation. Despite these changes, five patients in each group showed a fall of arterial Po2 of 5 mm. Hg or more. This was accompanied by an increase of alveolar-arterial oxygen tension gradient. It was concluded that the decreases of arterial blood Po2 resulted from reversal of pre-existing, compensatory, regional pulmonary vasoconstriction by the pulmonary vasodilator action of each drug in some subjects.